2022
DOI: 10.24820/ark.5550190.p011.773
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal lactams: a review

Abstract: Steroidal lactams are also a class of steroid derivatives that were synthesized and modified to increase the biological activity of steroids. Their synthesis is a stimulating challenge to the scientist, often claiming the development of new and generally useful reactions. Some of them have been tested successfully as anticancer drugs against different types of leukemia. Recent developments in the syntheses of steroidal lactams are described herein. The biological activities of those steroidal derivatives for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Structure containing D-homo lactone moiety and ester of p-bis(2-chloroethyl)aminophenylacetic acid on C3 (27), along with its lactam analogs 28 and 29, are proven to be effective in causing markedly increased SCE (sisterchromatid exchange) rates and cell division delays in human lymphocytes [123]. In more recent research, compounds 27 and 28 showed good anticancer activity against pancreatic cancer cell lines [124,125]. The best GI 50 of 8 µM is observed for D-homo lactam 28 on Hs776T cells.…”
Section: Biologically Active Derivatives and Analogs Of Testolactonementioning
confidence: 99%
“…Structure containing D-homo lactone moiety and ester of p-bis(2-chloroethyl)aminophenylacetic acid on C3 (27), along with its lactam analogs 28 and 29, are proven to be effective in causing markedly increased SCE (sisterchromatid exchange) rates and cell division delays in human lymphocytes [123]. In more recent research, compounds 27 and 28 showed good anticancer activity against pancreatic cancer cell lines [124,125]. The best GI 50 of 8 µM is observed for D-homo lactam 28 on Hs776T cells.…”
Section: Biologically Active Derivatives and Analogs Of Testolactonementioning
confidence: 99%
“…Their use in photopolymerization has been widely reported by Dumur and coworkers. 62 , 63 , 64 Coumarins are flavonoid type of secondary metabolites present in (green) plants and have been intensively studied due to promising antioxidant and anti-cancer properties. 65 Moreover, coumarins have been used in sensing, detecting or fluorescence applications.…”
Section: Natural Photoinitiating Systemsmentioning
confidence: 99%
“…However, with proper derivatization and substitution of the chalcone core, the photoelectric properties can be fine-tuned and shifted to the blue-green region. 63…”
Section: Natural Photoinitiating Systemsmentioning
confidence: 99%